KOMUNIKASI ORGANISASI TERHADAP MOTIVASI KERJA PEGAWAI PADA KANTOR BADAN PENDAPATAN DAERAH DI KABUPATEN BANYUASIN - Mutialela, Ratu; Amelia, Tiara (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2022)
Effective communication will create a healthy and open office work climate. This is very important to focus the creativity and dedication of office employees. The purpose of this study is to determine the effect of organizational communication on employee work motivation at the Regional Revenue Agency of Banyuasin Regency. The method used in this research is quantitative research. This research took place at the Regional Revenue Agency Office of Banyuasin Regency. The population in this study were the employees of the State Civil Apparatus (ASN) of the Regional Revenue Agency (BAPENDA) Banyuasin Regency, totaling 74 people. The sample was selected by the Disproportionate Stratified Random Sampling method with a total of 74. The instrument in this study used a questionnaire. Data collection techniques with observation and documentation. Data analysis with validity test, reliability test, and multiple linear regression test. The results show that the motivation variable (X1) and the communication variable (X2) together have an effect on employee performance (Y) at the Banyuasin Regional Revenue Agency.